Iron removal from groundwater using granular activated carbon filters by oxidation coupled with the adsorption process - Thinojah, T.; Ketheesan, B. (Journal of Water and Climate Change Vol 13 No 5, 1985 doi: 10.2166/wcc.2022.126, 2022)
Granular activated carbon (GAC) is commonly used as an adsorbent for the removal of organic micropollutants. However, little is known about the inorganic pollutant removal using GAC. In this study, GAC was examined for the removal of iron from synthetic groundwater (SGW) using oxidation coupled with an adsorption mechanism. Batch experiments including kinetic and isotherm studies were carried out to find out the adsorption capacity of GAC. A column test was conducted at different phases to identify the influence of the initial concentration of iron, hydraulic retention time (HRT), and air supply to the system. It was observed that the experimental results for the kinetic experiment best fit the pseudo-first-order kinetics model with 88% maximum removal efficiency achieved in 240 min. A reduction in adsorption capacity was observed with the concomitant increase in the weight of GAC, whereas the maximum adsorption capacity of GAC was found to be 0.17 mg Fe/g GAC. Column experiments confirmed that the effluent iron concentration reduced from 0.05 to 0.03 mg/L when the iron concentration in the influent increased from 1 to 3 mg/L. The reduction in HRT from 7 to 3.5 h did not significantly affect the iron removal efficiency. The air supply to the system with the flow rate of 3.5 L/min did not show any improvement in the iron removal efficiency due to the increased airflow rate. In all cases, the iron level in the effluent satisfied the drinking water quality standard recommended by the World Health Organization (WHO) which affirms that GAC filters are more suitable for iron removal from groundwater.
Keywords: Adsorption; Granular activated carbon; Iron removal; Oxidation; Synthetic groundwater